Perencanaan Instalasi Listrik di Hotel dan Villa Maua Nusa Penida - I Wayan Dikse Pancane; Ronal M Silitonga; I Made Asna (Jurnal Ilmiah Telsinas, 2022)
Maua Nusa Penida is one of the hotels and villas in Nusa Penida which will be discussed in this research. The number of hotel blocks to be built is 4 blocks, where each block consists of 8 rooms. As for the villa as many as 26 various villas. There is also a main building and a restaurant that will serve as future support. Once the existing buildings are complex, the developers are required to plan all the buildings to be built in order to obtain security and also economic factors in the development process. From the results of the planning that has been carried out on each building, each building requires a different number of lights depending on the type of lamp, the type of building and also the area of the building. After getting the total electricity demand in a building, planning is continued by determining the area of cable conductors that supply each building. From the calculation results, it is also known that the type of cable used is planting cable (NYRGbY & NYFGbY) which has good insulation when planted in the ground and follows the provisions of PLN regarding voltage loss, which does not exceed 5% at the end of the conductor. The safety used in buildings uses MCB and also MCCB. Meanwhile, the safety of electric current in the LVMDP and SDP sections uses MCCB components. From the planning results, the total electricity demand is 159,441VA for zone 1 villas and also 142,536VA for zone 2 villas. From this calculation it is also known that the PLN power requirement in each zone is 164,000 VA. To get the convenience and reliability of the electrical system in this hotel and villa, the supply of electrical power in addition to the electricity source from PLN is also equipped with a backup power generator of 200 KVA in each zone.